Modeling infiltration capacity of permeable channels under static and dynamic hydraulic conditions - Al-Janabi, Ahmed Mohammed Sami (2018)
Increasing infiltration rate of stormwater is important for improving the control of stormwater quantity to foster sustainable urban stormwater management. In the design of stormwater channels, the effect of infiltration on the channel flow and the effects of hydraulic parameters such as water level, channel cross section, flow velocity, and vegetation, on the infiltration capacity of channels are usually ignored. The present study aimed to examine the effects of hydraulic parameters on the infiltration capacity of permeable channels through laboratory investigation on channel models under static and dynamic hydraulic conditions. The study also aimed to develop empirical models for the variations of infiltration capacity with flow hydraulic parameters, in order to improve the design of permeable stormwater channels. Different channel models were constructed for each of the above condition, and different sets of hydraulic and channel boundary conditions were used to characterise the channel flow considering the effect of infiltration and to develop empirical models for predicting infiltration capacity for permeable channels. The effect of channel cross section on the flow reduction by seepage and infiltration processes were first examined under static or standing water condition, with various initial water levels, channel base widths and side slopes. Regression analysis was used to develop an equation for predicting the rate of unsteady seepage over time, and the equation was used to examine several cases of different flow cross-sectional areas and channel dimensions, and subsequently, to determine the section that produced highest infiltration and seepage under the unsaturated soil condition. Moreover, five existing infiltration models, namely, the Kostiakov, Horton, Modified Kostiakov, Philip, and Soil Conservation Service (SCS) models were evaluated, and then they were modified by incorporating the cross-sectional flow area parameters (depth y, side slope m, and bottom width b) into them. Under the dynamic or flowing water condition, the mass-balance method was used for the estimation of infiltration rate, and the experimental tests employed five inflow rates (Qin = 5.5, 7.5, 9.5, 11.5, 13.5 l/s), with three downstream check dam heights (hw = 10, 15, 20 cm). In addition, two other sets of experiments were conducted to investigate the effects of grass cover and subsurface water on infiltration rate. The findings were used to quantify and compare the different cases in terms of the infiltration rate and cumulative infiltration, and then to develop predictive equations that include the effect of hydraulic parameters for estimating the infiltration rate in permeable channels. The results indicated that the infiltration and seepage rates increase with increasing initial water level irrespective of the base width and side slope. Moreover, an increase in the side slope increases both the infiltration and seepage rates, with the effect becoming more significant as the initial water level increases, while the effect of varying the base width is insignificant. It has also been found that increasing the wetted perimeter or top width of a channel enhances the infiltration rate if this is achieved by varying the side slope, and not by increasing the base width. In the evaluation of the five infiltration models, a comparison using the coefficients of determination R2 obtained before and after the parameters were added into the models reveals that the difference between the observed and predicted values using the modified models was significantly reduced, and R2 increased sharply from 0.14, 0.158, 0.164, 0.146 and 0.162 for the Kostiakov, Horton, Modified Kostiakov, Philip, and SCS models, respectively, to 0.732, 0.621, 0.735, 0.718 and 0.609. Two predictive equations were developed finally using the nonlinear regression analysis after introducing the four hydraulic parameters (y, m, b and v) into the Kostiakov and Modified Kostiakov models, which were chosen to be improved because they have been shown to give better performance than the other models during the previous analysis. The latter model with the new parameters was used for the analysis of a channel section to determine the best conditions to obtain the highest infiltration rates for given flow rates and then to plot graphs of the variation of cumulative infiltration F over time for a grassed channel with different check dam heights and inflow rates. Cumulative infiltration quantity after 90 min for two cases of channels, with and without check dams, were compared and the results reveal that the percentage of total infiltrated water volume increased from 8% to 14% when using check dams with 20- cm height and 10-m spacing compared to the channel without the check dams. Modeling the variations of infiltration capacity with hydraulic parameters in permeable channels using the models developed in this study therefore promises better storm water management and provides a valuable decision support tool for designing the permeable channels.